Considerations for Acute and Emergent Deployed Mental Health Patient Management and Theater Transports: A Scoping Review. Issue 9 (28th August 2021) - Migliore, Laurie; Braun, Lisa; Stucky, Christopher H; Gardner, Cubby; Huffman, Sarah; Jumpp, Savannah; Bell, Emily
ABSTRACT: Background: Although combat stress and psychiatric casualties of war have consistently contributed to the need for deployed patient transport to higher echelons of care, little is known regarding specific evidence-based strategies for providing psychological support and optimal transport interventions for warriors. Study Objective: The purpose of this scoping review is to map existing literature related to considerations for deployed mental health patient transport. The review's primary aims are to identify the existing scientific research evidence, determine research and training gaps, and recommend critical areas for future military research. Methods: We used Arksey and O'Malley's six-stage scoping review methodological framework (identify the research question, identify relevant studies, select studies, chart data, report results, and consultation). Using a systematic search strategy, we evaluated peer-reviewed literature from five databases (PubMed, CINAHL, PsycINFO, Web of Science, and Embase) and gray literature from the Defense Technical Information Center. All publications were independently screened for eligibility by two researchers during three review rounds (title, abstract, and full text). Results: We identified 1, 384 publications, 61 of which met our inclusion criteria. Most publications and technical reports were level IV evidence and below, primarily retrospective cohort studies and epidemiologic surveillance reports. Few rigorously designed studies were identified. Eight research themes and a variety of research and critical training gaps were derived from the reviewed literature. Themes included (1) characterizing mental health patients aeromedically evacuated from theater; (2) in-flight sedation medications; (3) need for aeromedical evacuation (AE) in-theater education, training, and guidelines for staff; (4) epidemiological surveillance of AE from theater; (5) mental health management in deployed settings; (6) suicide-related event management; (7) transport issues for mental health patients; and (8) psychological stressors of AE. Research is needed to establish clinical practice guidelines for mental health condition management in theater and throughout the continuum of en route care.